A method for preparing microsphere nanocomposite material
By combining NiO/Ni nanoparticles with sulfur-rich vacancies, NiO/Ni@ZCS-Vs microspheric nanocomposites are constructed, which solves the problem of limited photocatalytic performance of existing ZnxCd1-xS materials and achieves efficient photocatalytic hydrogen production.
Patent Information
- Application Number
- CN202411658864.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-11-20
AI Technical Summary
The performance of existing ZnxCd1-xS materials in photocatalytic decomposition of water hydrogen analysis is limited by its intrinsic defects and narrow spectral response, especially the photocatalytic performance of the composite catalyst of sulfur-rich ZnxCd1-xS with metal-based or metal oxide nanoparticle is poorly understood.
NiO/Ni nanoparticles were compounded with sulfur-rich vacancies by sol-gel method, and co-assembled through the carbonaceous layer as an intermediate mediated interface to construct NiO/Ni@ZCS-Vs microspheric nanocomposites to form p-n junctions to optimize the transfer of electrons and holes.
The photocatalytic hydrogen production performance of ZnxCd1-xS material is significantly improved, its response and absorption capacity to visible light is enhanced, carrier separation and migration efficiency is improved, and more hydrogen production active sites are provided.
Smart Images

Figure CN119140122B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solar energy and photocatalytic hydrogen production, and in particular to a method for preparing a microsphere nanocomposite material. Background Art
[0002] Ternary zinc cadmium sulfide (hereinafter referred to as Zn x Cd 1-x ZnS has the advantages of simple synthesis, good chemical stability, adjustable band structure, and sensitivity to visible light. Compared with similar ZnS and CdS, it has superior photocatalytic performance. However, due to its intrinsic defects, such as rapid recombination between electrons and holes, slow charge transfer, and narrow spectral response, the further practical application of this material is limited. The ZnS photocatalytic performance can be further improved by utilizing various strategies, such as nanostructure engineering, element doping, defect engineering, loading of precious metals (Ag, Pt, etc.), photosensitive composite materials, construction of heterojunctions, and introduction of co-catalysts. x Cd 1-x S photocatalytic activity. Among them, defect engineering is an important strategy for controllable modification of electronic structure and charge transfer dynamics. At the same time, morphology regulation has an important impact on the photocatalytic activity of Zn x Cd 1-x The photocatalytic activity of sulfur is also of great significance. x Cd 1- x S particles have high visible light hydrogen production activity. x Cd 1-x Little is known about the photocatalytic performance of S-based composite catalysts with metal-based or metal oxide nanoparticles for hydrogen evolution from water. Summary of the invention
[0003] To this end, the present invention provides a method for preparing a microsphere nanocomposite material, and the microsphere nanocomposite material can be used for photocatalytic efficient hydrogen production.
[0004] The present invention adopts the following technical scheme: a method for preparing a microsphere nanocomposite material, comprising the following steps:
[0005] (1) Take a certain amount of Zn(AC)2·2H2O (zinc acetate dihydrate) and Cd(NO3)2·4H2O and stir them thoroughly to dissolve them in a mixed solution of appropriate amount of deionized water and hydrazine hydrate, then add a certain amount of CH4N2S (thiourea) and continue stirring at room temperature for 10-120 minutes;
[0006] (2) pouring the mixed solution stirred evenly in step (1) into the inner lining of a hydrothermal reactor, heating at a certain temperature, keeping the temperature for 6-24 hours and then cooling to room temperature, washing the obtained product with deionized water and ethanol several times, and vacuum drying to obtain a ZCS-Vs powder rich in sulfur vacancy defects that can act as electron traps;
[0007] (3) Dissolve a certain amount of glucose, NiCl2·6H2O and urea in an appropriate amount of deionized water and stir for 10-240 minutes;
[0008] (4) Pour the uniformly stirred solution in step (3) into the inner lining of a hydrothermal reactor, heat it at a certain temperature, keep it warm for 6-24 hours, and then cool it to room temperature. Wash the obtained product with deionized water and ethanol several times, and vacuum dry it to obtain a black precursor Ni(OH)2@C powder;
[0009] (5) pouring an appropriate amount of the Ni(OH)2@C powder obtained in step (4) into a porcelain boat, placing the boat in a tube furnace, introducing N2 for 10-60 min to remove air, and then heating the boat to 300-500°C at a certain heating rate in a N2 atmosphere, and keeping the temperature for 30-240 min. After natural cooling, a NiO / Ni@C powder with a black coral ball morphology and a multilayer core-shell structure is obtained, wherein NiO and Ni form an ohmic junction;
[0010] (6) ultrasonically dispersing a certain amount of NiO / Ni@C obtained in step (5) in a certain amount of deionized water solution prepared with ZCS-Vs, and stirring at room temperature for 1-24 h;
[0011] (7) The mixed solution stirred evenly in step (6) is placed in a muffle furnace, heated to 300-500°C at a certain heating rate in an air atmosphere, and kept warm for 60-720 minutes. After natural cooling, a yellow-green powder is obtained, which is named as X% NiO / Ni@ZCS-Vs microsphere nanocomposite material, where X% is the mass ratio of NiO / Ni@C to ZCS-Vs. The NiO in the microsphere nanocomposite material forms a pn junction with ZCS-Vs, and the whole has excellent carrier separation and migration characteristics, and efficient photocatalytic hydrogen production performance.
[0012] Preferably, the mass of Zn(AC)2·2H2O used in step (1) is 0.1-10 g, the mass of Cd(NO3)2·4H2O is 0.1-10 g, the volume ratio of deionized water to hydrazine hydrate mixed solution is 1-20%, the volume is 10-500 mL, and the mass of CH4N2S is 0.1-10 g.
[0013] Preferably, in step (2), the heating temperature is 120-350°C, the vacuum drying temperature is 40-90°C, and the time is 6-24h.
[0014] Preferably, the mass of glucose used in step (3) is 0.1-15 g, the mass of NiCl2·6H2O is 0.1-10 g, the mass of urea is 0.1-15 g, and the volume of deionized water is 2-1000 mL.
[0015] Preferably, in step (4), the heating temperature is 100-300°C, the vacuum drying temperature is 40-90°C, and the time is 6-24h.
[0016] Preferably, the heating rate in step (5) is 1-20°C·min -1 .
[0017] Preferably, the mass of NiO / Ni@C used in step (6) is 0.1-10 g, the mass of ZCS-Vs is 0.1-10 g, and the volume of deionized water is 10-200 mL.
[0018] Preferably, the heating rate in step (7) is 1-20°C·min -1 .
[0019] Compared with the prior art, the present invention has the advantages of: by using the sol-gel method to composite NiO / Ni nanoparticles with ZCS-Vs using the carbonaceous layer as an intermediate, a NiO / Ni@ZCS-Vs microsphere nanocomposite material is constructed, which significantly improves the Zn x Cd 1-x The response and absorption capacity of the S matrix material to light is improved, and its energy band structure is optimized, which improves the separation and transfer capacity of photogenerated electrons and holes. The obtained NiO / Ni@ZCS-Vs microsphere nanocomposite material has the advantages of stable structure, strong visible light response ability, high carrier separation efficiency, rich hydrogen production active sites, simple preparation process, and low production cost. It can be applied to solar energy and photocatalytic efficient hydrogen production. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The XRD (X-ray diffraction) diagrams of different samples provided by the embodiments of the present invention are shown.
[0021] Figure 2 The TEM (transmission electron microscope) image, HRTEM (high resolution transmission electron microscope) image lattice and defects, and SEM (scanning electron microscope) images of 6% NiO / Ni@ZCS-Vs microsphere nanocomposite prepared in Example 1 are shown.
[0022] Figure 3 A graph showing the photocatalytic hydrogen production rates of different samples provided in an embodiment of the present invention is shown. DETAILED DESCRIPTION
[0023] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention.
[0024] The present invention provides a method for preparing a microsphere nanocomposite material. The microsphere nanocomposite material (NiO / Ni@ZCS-Vs) is a highly efficient hydrogen production photocatalytic material. The design idea of the present invention is to introduce NiO / Ni nanoparticles into the Zn x Cd 1-x S can optimize its electronic band structure, improve light absorption capacity and photogenerated carrier lifetime, and provide more active sites for hydrogen production. The ohmic junction formed between NiO and Ni will act as an "accelerator pump" for electron transmission, accelerating the transfer of photogenerated carriers. x Cd 1-x The pn junction formed between S and Ni compounds can promote the transfer of electrons and holes, effectively promote the decomposition of water under visible light irradiation, and significantly improve the photocatalytic hydrogen production activity of the material. Therefore, it is an effective strategy to improve the photocatalytic efficiency to composite NiO / Ni nanoparticles with ZCS-Vs using carbonaceous layers as intermediates to further improve the carrier separation efficiency and provide more hydrogen production active sites.
[0025] Specifically, the present invention uses a sol-gel method to realize the synthesis of NiO / Ni and Zn with abundant sulfur vacancies. 0.5 Cd 0.5 S (hereinafter referred to as ZCS-Vs) is co-assembled at the interface mediated by a carbon template as an intermediate to construct a NiO / Ni@ZCS-Vs microsphere nanocomposite material with tight interface bonding, stable structure, strong visible light response ability, high electron transfer efficiency and abundant catalytic active sites, which can be used for photocatalytic efficient hydrogen production.
[0026] In order to illustrate the technical solution described in this application, a specific embodiment is provided below for illustration. Example 1
[0027] The invention discloses a method for preparing a microsphere nanocomposite material.
[0028] (1) 0.55g of Zn(AC)2·2H2O and 0.75g of Cd(NO3)2·4H2O were used as raw materials and fully dissolved in 40mL of deionized water solution containing 8 vol.% hydrazine hydrate by stirring. Then 0.45g of CH4N2S was added to the solution and stirred continuously at room temperature for 40min. The solution was then transferred to the inner lining of a hydrothermal kettle and kept at 200℃ for 14h before cooling to room temperature. The cooled product was precipitated by centrifugation and washed several times with deionized water and ethanol. Finally, it was vacuum dried at 70℃ for 10h to obtain yellow ZCS-Vs powder.
[0029] (2) 1.08 g of glucose, 0.48 g of NiCl2·6H2O and 1.2 g of urea were used as raw materials and fully dissolved in 40 mL of deionized water by stirring. The solution was then transferred into the inner lining of a hydrothermal reactor and kept at 160 °C for 10 h before being cooled to room temperature. The cooled product was collected by centrifugation and precipitated, washed several times with deionized water and ethanol, and finally dried in vacuum at 70 °C for 10 h to obtain a black precursor Ni(OH)2@C powder. The Ni(OH)2@C powder was placed in a tubular furnace and N2 was introduced for 20 min. The powder was then heated at 5 °C·min under N2 atmosphere. -1 The temperature was raised to 420°C and kept at 420°C for 2 h, and black NiO / Ni@C powder was obtained after cooling;
[0030] (3) 0.12 g NiO / Ni@C was ultrasonically dispersed in 100 mL of deionized water prepared with 2 g ZCS-Vs and stirred at room temperature for 8 h. The solution was then placed in a muffle furnace and heated at 6 °C min-1 in an air atmosphere. -1 The temperature was raised to 420°C, kept for 3 hours, and cooled to obtain a 6% NiO / Ni@ZCS-Vs microsphere nanocomposite material, wherein 6% is the mass ratio of NiO / Ni@C to ZCS-Vs.
[0031] Therefore, by adjusting the ratio between the raw materials, NiO / Ni@ZCS-Vs microsphere nanocomposites with different mass ratios can be prepared, that is, X% NiO / Ni@ZCS-Vs microsphere nanocomposites, where X% is the mass ratio of NiO / Ni@C to ZCS-Vs. For example, NiO / Ni@ZCS-Vs microsphere nanocomposites with different mass ratios such as 6.7%, 6%, 5%, 3%, 8%, and 10% can be prepared.
[0032] As an example, Figure 1The XRD patterns of different samples provided in the embodiments of the present invention are shown. For example, these different samples include five samples: 8% NiO / Ni@ZCS-Vs microsphere nanocomposite material, 10% NiO / Ni@ZCS-Vs microsphere nanocomposite material, ZCS-Vs, NiO:PDF#44-1159, ZCS:PDF#49-1302, Ni:PDF#04-0850, etc. Among them, the abscissa represents the 2θ angle (°), and the ordinate represents the intensity (au).
[0033] It should be noted that the above ZCS-Vs can be understood as Zn x Cd 1-x S, ZCS can be understood as Zn without sulfur vacancy defects x Cd 1-x S.
[0034] As an example, in Figure 1 In the figure, (101), (012), (111), (200), (110), and (220) represent the 101 crystal plane, 012 crystal plane, 111 crystal plane, 200 crystal plane, 110 crystal plane, and 220 crystal plane of 10%NiO / Ni@ZCS-Vs microsphere nanocomposite material, respectively.
[0035] As an example, in Figure 1 , (100), (002), (101), (102), (110), (103), and (112) represent the 100, 002, 101, 102, 110, 103, and 112 planes of ZCS-Vs, respectively.
[0036] As an example, Figure 2 The TEM image, HRTEM image lattice and defects, and SEM images at different magnifications of the 6% NiO / Ni@ZCS-Vs microsphere nanocomposite prepared in Example 1 are shown.
[0037] As an example, area (a) is a TEM image of a 6% NiO / Ni@ZCS-Vs microsphere nanocomposite material with a scale of 100 nm. For example, area (a) also shows the positional relationship between ZCS-Vs, Ni, and NiO.
[0038] As an example, (b) and (c) regions constitute the HRTEM image lattice and defects of 6% NiO / Ni@ZCS-Vs microsphere nanocomposite.
[0039] For example, area (b) is a partial enlarged view of area (a), and area (c) is a partial enlarged view of area (b). Specifically, area (b) shows the HRTEM image lattice and defects with a scale of 10nm, and area (c) shows the HRTEM image lattice and defects with a scale of 2nm. At the same time, area (c) is an enlarged view of the elliptical dotted box in area (b). In addition, a partial enlarged view of the boxed area in area (b) is shown in the upper right corner of area (b).
[0040] Exemplarily, in region (b), it is also shown that the interplanar spacing d of the 002 crystal plane of ZCS-Vs is 0.33 nm.
[0041] As an example, the (d) area is a SEM image with a scale of 10 μm, and the (e) area is a SEM image with a scale of 5 μm. Example 2
[0042] The invention discloses a method for preparing a microsphere nanocomposite material.
[0043] (1) 1.1g of Zn(AC)2·2H2O and 1.5g of Cd(NO3)2·4H2O were used as raw materials and fully dissolved in 80mL of deionized water solution containing 10 vol.% hydrazine hydrate by stirring. Then 0.9g of CH4N2S was added to the solution and stirred continuously at room temperature for 60min. The solution was then transferred to the inner lining of a hydrothermal kettle and kept at 220℃ for 12h before cooling to room temperature. The cooled product was precipitated by centrifugation and washed several times with deionized water and ethanol. Finally, it was vacuum dried at 60℃ for 12h to obtain yellow ZCS-Vs powder.
[0044] (2) 0.54 g glucose, 0.24 g NiCl2·6H2O and 0.6 g urea were used as raw materials and fully dissolved in 20 mL deionized water by stirring. The solution was then transferred into the inner lining of a hydrothermal reactor and kept at 180 °C for 8 h before cooling to room temperature. The cooled product was collected by centrifugation and precipitated, washed several times with deionized water and ethanol, and finally dried under vacuum at 60 °C for 12 h to obtain a black precursor Ni(OH)2@C powder. The Ni(OH)2@C powder was placed in a tubular furnace and N2 was introduced for 30 min. Then, the mixture was heated at 7 °C·min under N2 atmosphere. -1 The temperature was raised to 400°C and kept at 400°C for 1 h, and black NiO / Ni@C powder was obtained after cooling;
[0045] (3) 0.08 g NiO / Ni@C was ultrasonically dispersed in 50 mL deionized water solution containing 1 g ZCS-Vs and stirred at room temperature for 6 h. The solution was then placed in a muffle furnace and heated at 5 °C min-1 under air atmosphere. -1The temperature was raised to 400°C, kept at this temperature for 4 hours, and then cooled to obtain 8% NiO / Ni@ZCS-Vs microsphere nanocomposite material. Example 3
[0046] The invention discloses a method for preparing a microsphere nanocomposite material.
[0047] (1) 2.2 g of Zn(AC)2·2H2O and 3.0 g of Cd(NO3)2·4H2O were used as raw materials and fully dissolved in 160 mL of deionized water solution containing 12 vol.% hydrazine hydrate by stirring. Then 1.8 g of CH4N2S was added to the solution and stirred continuously at room temperature for 90 min. The solution was then transferred to the inner lining of a hydrothermal kettle and kept at 240°C for 10 h before cooling to room temperature. The cooled product was precipitated by centrifugation and washed several times with deionized water and ethanol. Finally, it was vacuum dried at 80°C for 8 h to obtain yellow ZCS-Vs powder.
[0048] (2) 1.62 g of glucose, 0.72 g of NiCl2·6H2O and 1.8 g of urea were used as raw materials and fully dissolved in 60 mL of deionized water by stirring. The solution was then transferred to the inner lining of a hydrothermal reactor and kept at 200 °C for 6 h before being cooled to room temperature. The cooled product was collected by centrifugation and precipitated, washed several times with deionized water and ethanol, and finally dried in vacuum at 80 °C for 8 h to obtain a black precursor Ni(OH)2@C powder. The Ni(OH)2@C powder was placed in a tubular furnace and N2 was introduced for 60 min. The powder was then heated at 9 °C·min under N2 atmosphere. -1 The temperature was raised to 450°C and kept at 450°C for 3 h, and black NiO / Ni@C powder was obtained after cooling;
[0049] (3) 0.3 g NiO / Ni@C was ultrasonically dispersed in 150 mL of deionized water prepared with 3 g ZCS-Vs and stirred at room temperature for 10 h. The solution was then placed in a muffle furnace and heated at 8 °C min-1 under air atmosphere. -1 The temperature was raised to 480°C, kept at this temperature for 5 h, and then cooled to obtain a 10% NiO / Ni@ZCS-Vs microsphere nanocomposite material. Example 4
[0050] The photocatalytic performance was tested. The photocatalytic hydrogen evolution reaction was carried out in a top-irradiated Pyrex reactor connected to a glass-enclosed gas circulation system at room temperature. In detail, 50 mg of catalyst powder (i.e., NiO / Ni@ZCS-Vs microsphere nanocomposite) was added to 100 ml of lactic acid (20 vol.%) solution, ultrasonically dispersed for 30 min, and then transferred to the top-irradiated photoreactor. Before visible light irradiation, the reactor was fixed on the hydrogen production instrument, and the reaction system was ensured to be under anaerobic conditions by vacuum pumping air and multiple gas washing operations (alternating vacuuming and filling with carrier gas), and circulating water cooling (6 ° C) was turned on. A 300 W xenon lamp was used as the light source to generate H2 under magnetic stirring conditions, and the amount of H2 generated was detected by a thermal conductivity detector and a gas chromatograph. The experiment was carried out for 3 h, and the hydrogen production was measured every 0.5 h.
[0051] As an example, Figure 3 The photocatalytic hydrogen production rate diagram of different samples provided in the embodiment of the present invention is shown. The different samples include: NiO / Ni@ZCS-Vs microsphere nanocomposites with five mass ratios of 6.7%, 5%, 3%, 8%, and 10%, as well as ZCS-Vs rich in sulfur vacancy defects and ZCS without sulfur vacancy defects.
[0052] like Figure 3 As shown, the X-axis represents different samples, the Y-axis represents the illumination time (h), and the unit of the Z-axis is mmol / g, which represents the amount of millimoles of hydrogen produced per gram of sample.
[0053] Therefore, the analysis Figure 3 From the data shown, we can know that:
[0054] (1) Overall, the photocatalytic hydrogen production efficiency of the NiO / Ni@ZCS-Vs microsphere nanocomposites with five mass ratios is greater than that of ZCS-Vs, and the hydrogen production efficiency of ZCS-Vs is greater than that of ZCS.
[0055] (2) In detail, the photocatalytic hydrogen production efficiency of the five mass ratios of NiO / Ni@ZCS-Vs microsphere nanocomposites is as follows from high to low: 6.7% NiO / Ni@ZCS-Vs microsphere nanocomposites, 5% NiO / Ni@ZCS-Vs microsphere nanocomposites, 3% NiO / Ni@ZCS-Vs microsphere nanocomposites, 8% NiO / Ni@ZCS-Vs microsphere nanocomposites, and 10% NiO / Ni@ZCS-Vs microsphere nanocomposites. Therefore, for the NiO / Ni@ZCS-Vs microsphere nanocomposites with a mass ratio of 3% to 10%, the photocatalytic hydrogen production efficiency is high in the middle and low on both sides. Specifically, the photocatalytic hydrogen production efficiency of 6.7% NiO / Ni@ZCS-Vs microsphere nanocomposite material is the highest, and when the mass ratio is less than 6.7%, the larger the mass ratio, the higher the photocatalytic hydrogen production efficiency, and when the mass ratio is greater than 6.7%, the larger the mass ratio, the lower the photocatalytic hydrogen production efficiency.
[0056] In summary, the NiO / Ni@ZCS-Vs microsphere nanocomposite material prepared in the embodiment of the present application has a good photocatalytic hydrogen production effect, a high hydrogen production amount and a high hydrogen production rate per gram of sample, and for NiO / Ni@ZCS-Vs microsphere nanocomposite materials with different mass ratios (3%~10%), the photocatalytic hydrogen production efficiency is high in the middle and low on both sides.
[0057] Without limitation to this, any changes or substitutions that are not conceived through creative work should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope defined in the claims.
Claims
1. A method for preparing a microsphere nanocomposite material, characterized in that: The following steps are involved: (1) Take a certain amount of Zn(AC)2·2H2O and Cd(NO3)2·4H2O and stir them thoroughly to dissolve them in a mixed solution of appropriate amount of deionized water and hydrazine hydrate, then add a certain amount of CH4N2S and continue stirring at room temperature for 10-120 minutes; (2) pouring the mixed solution stirred evenly in step (1) into the inner lining of a hydrothermal kettle, heating at a certain temperature, keeping the temperature for 6-24 hours, and then cooling to room temperature, washing the obtained product with deionized water and ethanol for several times, and vacuum drying to obtain ZCS-Vs powder; (3) Dissolve a certain amount of glucose, NiCl2·6H2O and urea in an appropriate amount of deionized water and stir for 10-240 minutes; (4) Pour the uniformly stirred solution in step (3) into the inner lining of a hydrothermal reactor, heat it at a certain temperature, keep it warm for 6-24 hours, and then cool it to room temperature. Wash the obtained product with deionized water and ethanol several times, and vacuum dry it to obtain a black precursor Ni(OH)2@C powder; (5) pouring an appropriate amount of the Ni(OH)2@C powder obtained in step (4) into a porcelain boat, placing the boat in a tube furnace, introducing N2 for 10-60 min to remove air, and then heating the boat to 300-500°C at a certain heating rate in a N2 atmosphere, and keeping the temperature for 30-240 min, and then cooling the boat naturally to obtain black NiO / Ni@C powder; (6) ultrasonically dispersing a certain amount of NiO / Ni@C obtained in step (5) in a certain amount of deionized water solution prepared with ZCS-Vs, and stirring at room temperature for 1-24 h; (7) The mixed solution stirred evenly in step (6) is placed in a muffle furnace, heated to 300-500° C. at a certain heating rate in an air atmosphere, and kept warm for 60-720 min. After natural cooling, a yellow-green powder is obtained, which is named as X% NiO / Ni@ZCS-Vs microsphere nanocomposite material, where X% is the mass ratio of NiO / Ni@C to ZCS-Vs.
2. The method for preparing a microsphere nanocomposite material according to claim 1, characterized in that: The mass of Zn(AC)2·2H2O used in step (1) is 0.1-10g, the mass of Cd(NO3)2·4H2O is 0.1-10g, the volume ratio of deionized water to hydrazine hydrate mixed solution is 1-20%, the volume is 10-500mL, and the mass of CH4N2S is 0.1-10g.
3. The method for preparing a microsphere nanocomposite material according to claim 1, characterized in that: In step (2), the heating temperature is 120-350°C, the vacuum drying temperature is 40-90°C, and the time is 6-24h.
4. The method for preparing a microsphere nanocomposite material according to claim 1, characterized in that: The mass of glucose used in step (3) is 0.1-15 g, the mass of NiCl2·6H2O is 0.1-10 g, the mass of urea is 0.1-15 g, and the volume of deionized water is 2-1000 mL.
5. The method for preparing a microsphere nanocomposite material according to claim 1, characterized in that: In step (4), the heating temperature is 100-300°C, the vacuum drying temperature is 40-90°C, and the time is 6-24h.
6. The method for preparing a microsphere nanocomposite material according to claim 1, characterized in that: The heating rate in step (5) is 1-20°C·min -1 .
7. The method for preparing a microsphere nanocomposite material according to claim 1, characterized in that: The mass of NiO / Ni@C used in step (6) is 0.1-10 g, the mass of ZCS-Vs is 0.1-10 g, and the volume of deionized water is 10-200 mL.
8. The method for preparing a microsphere nanocomposite material according to claim 1, characterized in that: The heating rate in step (7) is 1-20°C·min -1 .
Citation Information
Patent Citations
Preparation method and application of Ni / NiO / N-C carbon-based catalyst for hydrogen production through water electrolysis
CN113073337A
Sulfur defect-containing zinc-cadmium-sulfur / nickel-cobalt hydroxide composite visible-light-driven photocatalyst and application thereof
CN113731424A